Hysteroscopic Evaluation in Infertile Women with IVF Failure - Kıran, Hakan; Çetin, Turan; Kaplanoğlu, Mustafa (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTİVE: The aim of this study was to investigate the hysteroscopic evaluation in infertil women with IVF failure. STUDY DESIGN: The results of 343 infertil women with IVF failure that were performed hysteroscopy were evaluated. RESULT: In a total of 343 women 238 (69%) were found to have normal endometrial cavities. In 31% of subjects, a pathology was observed; 72% of these women had endometrial polyps, 17% had uterine septum, 7% had leiomyomas and 4% had intrauterine synechia on hysteroscopic examination. CONCLUSION: The uterin pathology was observed in %31 of the infertile women. Endometrial polyps were most common uterine pathology in our study. Our recommendation is to plan hysteroscopy in infertil women with IVF failure.